2023
DOI: 10.1093/function/zqad023
|View full text |Cite
|
Sign up to set email alerts
|

The Molecular Circadian Clock of Phox2b-expressing Cells Drives Daily Variation of the Hypoxic but Not Hypercapnic Ventilatory Response in Mice

Abstract: While the suprachiasmatic nucleus (SCN) controls 24-hour rhythms in breathing including minute ventilation (VE), the mechanisms by which the SCN drives these daily changes are not well understood. Moreover, the extent to which the circadian clock regulates hypercapnic and hypoxic ventilatory chemoreflexes is unknown. We hypothesized that the SCN regulates daily breathing and chemoreflex rhythms by synchronizing the molecular circadian clock of cells. We used whole-body plethysmography to assess ventilatory fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…This indicates that light has the ability to immediately drive behavior independently of the SCN (also referred to as “light masking”). In line with this notion, we recently identified that mice lacking a functional molecular clock continue to exhibit a detectable daily rhythm in minute ventilation when housed on a standard light:dark cycle ( Jones et al, 2023 ). This suggests that, like some other behaviors, light can synchronize daily breathing rhythms independent of the circadian clock.…”
Section: Potential Mechanisms By Which Light Modulates Breathingmentioning
confidence: 77%
See 2 more Smart Citations
“…This indicates that light has the ability to immediately drive behavior independently of the SCN (also referred to as “light masking”). In line with this notion, we recently identified that mice lacking a functional molecular clock continue to exhibit a detectable daily rhythm in minute ventilation when housed on a standard light:dark cycle ( Jones et al, 2023 ). This suggests that, like some other behaviors, light can synchronize daily breathing rhythms independent of the circadian clock.…”
Section: Potential Mechanisms By Which Light Modulates Breathingmentioning
confidence: 77%
“…The SCN appears to entrain airway tissues via the vagal nerve ( Bando et al, 2007 ), however, it is currently unknown how the SCN confers timing to other respiratory structures. While it is unclear whether these other mechanisms contribute to daily breathing behavior, we recently demonstrated that eliminating molecular time-keeping specifically within respiratory cells of the autonomic nervous system abolishes circadian variation in the hypoxic ventilatory response ( Jones et al, 2023 ). This finding suggests that the circadian clock may organize daily breathing rhythms, in part, via the organization of clock genes in the neural respiratory network.…”
Section: Potential Mechanisms By Which Light Modulates Breathingmentioning
confidence: 99%
See 1 more Smart Citation